DNA hypermethylation/boundary control loss identified in retinoblastomas associated with genetic and epigenetic inactivation of the RB1 gene promoter. Issue 9 (2nd September 2021) - Raizis, AM; Racher, HM; Foucal, A; Dimaras, H; Gallie, BL; George, PM
ABSTRACT: DNA hypermethylation events occur frequently in human cancers, but less is known of the mechanisms leading to their initiation. Retinoblastoma, an intraocular cancer affecting young children, involves bi-allelic inactivation of the RB1 gene ( RB −/- ). RB1 encodes a tumour suppressing, cell cycle regulating transcription factor ( pRB) that binds and regulates the RB1 core and other E2F responsive promoters with epigenetic functions that include recruitment of histone deacetylases ( HDACs ). Evidence suggests that bi-allelic epigenetic inactivation/hypermethylation of the RB1 core promoter ( Pr E-/E- ), is specific to sporadic retinoblastomas (frequency 10%), whereas heritable RB1 promoter variants ( Pr −/+, frequency 1-2%) are not associated with known epigenetic phenomena. We report heritable Pr −/- retinoblastomas with the expected loss of pRB expression, in which hypermethylation consistent with distal boundary displacement (BD) relative to normal peripheral blood DNAs was detected in 4/4 cases. In contrast, proximal BD was identified in 16/16 RB −/- retinoblastomas while multiple boundaries distal of the core promoter was further identified in Pr E-/E- and Pr E-/E+ retinoblastomas. However, weak or no DNA hypermethylation/ BD in peripheral blood DNA was detected in 8/9 Pr −/+ patients, with the exception, a carrier of a microdeletion encompassing several RB1 promoter elements. These findings suggest that loss of boundary control may be a critical step leading to epigenetic inactivation of the RB1 gene and that novel DNA methylation boundaries/profiles identified in the RB1 promoter of Pr −/- retinoblastomas, may be the result of epigenetic phenomena associated with epimutation in conjunction with loss of pRB expression/binding and/or RB1 promoter interactions with boundary control elements.